Correlation Between Cervical Posture and Cervical Proprioception Among Chronic Smartphone Users (International Journal of Physiotherapy, 2024)
Background: The Smartphone, an invention of humanity, became an inherent part of human life. The gradual escalation of its use from a "habit" to an addiction is growing with a need to gauge them. It has been reported that smartphone users maintain head flexion of 33°–45°; continuation of this attitude may alter muscle length and its orientation, followed by a change in the joint position of the cervical spine. Cervical posture and proprioception are critical in postural stability, reflex activity, and head-and-eye coordination. Therefore, this study is conducted to assess the changes and determine and alleviate the adverse effects among chronic smartphone users.Methods: A non-experimental study design and correlational study type with a convenient sampling method were performed. One hundred ten participants of both genders aged 18-25 years from in and around Chennai were scrutinized for smartphone addiction. Participants' cervical posture and proprioception were assessed using the joint position error test and photogrammetry method for men and women who obtained more than or equal to 31 and 33, respectively.Results: This study shows a weak positive correlation between cervical posture and proprioception (r=0.053, p=0.715) among smartphone users.Conclusion: This study concludes that various medical ailments can be avoided with early intervention and adequate awareness concerning smartphone usage and its detrimental impacts. These findings shed light on the potential health risks associated with smartphone usage, providing valuable insights for medical professionals, researchers, and individuals.